Impact of ambulatory cardiac rehabilitation on cardiovascular outcomes: a long-term follow-up study. (27th July 2018) - Doimo, Sara; Fabris, Enrico; Piepoli, Massimo; Barbati, Giulia; Antonini-Canterin, Francesco; Bernardi, Guglielmo; Maras, Patrizia; Sinagra, Gianfranco
Abstract: Aims: To evaluate the long-term clinical impact of the application of cardiac rehabilitation (CR) early after discharge in a real-world population. Methods and results: We analysed the 5-year incidence of cardiovascular mortality and hospitalization for cardiovascular causes in two populations, attenders vs. non-attenders to an ambulatory CR program which were consecutively discharged from two tertiary hospitals, after ST-elevation myocardial infarction, non-ST-elevation myocardial infarction, coronary artery bypass graft, or planned percutaneous coronary intervention. A primary analysis using multivariable regression model and a secondary analysis using the propensity score approach were performed. Between 1 January 2009 and 31 December 2010, 839 patients attended a CR program planned at discharged, while 441 patients were discharged from Cardiovascular Department without any program of CR. During follow-up, the incidence of cardiovascular mortality was 6% in both groups ( P = 0.62). The composite outcome of hospitalizations for cardiovascular causes and cardiovascular mortality were lower in CR group compared to no-CR group (18% vs. 30%, P < 0.001) and was driven by lower hospitalizations for cardiovascular causes (15 vs. 27%, P < 0.001). At multivariable Cox proportional hazard analysis, CR program was independent predictor of lower occurrence of the composite outcome (hazard ratio 0.58, 95% confidence interval 0.43–0.77; P < 0.001), while in the propensity-matched analysis CR group experienced also a lower total mortality (10% vs. 19%, P = 0.002) and cardiovascular mortality (2% vs. 7%, P = 0.008) compared to no-CR group. Conclusion: This study showed, in a real-world population, the positive effects of ambulatory CR program in improving clinical outcomes and highlights the importance of a spread use of CR in order to reduce cardiovascular hospitalizations and cardiovascular mortality during a long-term follow-up.